Binding orientation and reactivity of alkyl α, ω-dibromides in water-soluble cavitands. Issue 21 (15th May 2019) - Angamuthu, Venkatachalam; Petroselli, Manuel; Rahman, Faiz-Ur; Yu, Yang; Rebek, Julius
Abstract : Host–guest complexation of α, ω-dibromides showed rabid tumbling conformation on NMR timescales and afforded mono hydroxyl bromides after hydrolysis in D2 O. Abstract : Host–guest complexation of long chain α, ω-dibromides was evaluated in deep water-soluble cavitands 1 and 2. The bound dibromides (C7 –C12 ) tumble rapidly on the NMR timescale and averaged signals were observed. The complexation allows mono hydrolysis of dibromides in aqueous solution. The arrangement of the products in the host–guest complex was fixed in an unsymmetrical manner that protects the guest from further reaction. Up to 93% yields of the mono-alcohols were obtained. The α, ω-dibromides formed a capsule with cavitand 2 and remained unreactive to hydrolysis.